Micropropagation of sweet marjoram (Majorana hortensis Moench) - PAI, P V IYER, J S (Journal of Spices and Aromatic Crops, 1998)
Multiple shoots were obtained in sweet marjoram (Majorana hortensis) when nodal stem explants were cultured on Murashige and Skoog medium containing 2 mgP6-benzylaminopurine. Rooting of shoots was induced with 0.2 mgP indolebutyric acid in the same medium.